The wind and the trees - Todd, Stewart (Owlkids Books, 2021)
"This picture book takes place in the serenity of a forest as a new pine seedling strikes up a conversation with a nearby older tree that will last for many years. Each beautifully illustrated spread shows the two trees, one on each side, as they discuss the wind, the younger tree learning from the experiences of the older: Wind feels good but it stretches trees and dries them out. It also makes trees dig in and build strength. Wind scatters seeds, and it carries messages and signals to other trees in the forest. As time passes, the younger tree becomes visibly larger, fuller, and more robust as the older tree thins and droops, needles stripped away, until it's little more than a trunk when a fierce storm blows through and takes it down, clearing old growth to make room for new. The story ends with the younger tree-now mature-greeting a seedling that floats in on the wind, taking root in the old tree's spot in the forest. Gorgeous multilayered screen prints show the trees in a wide variety of unexpected lights and colours, different on every spread, to reflect changing seasons, weather, moods, life stages, and more in this beautiful, textured art. On one level, the story sweetly honors intergenerational relationships, highlighting the value both trees have to offer, such as wisdom, nurturing, and mentoring on the part of the elder tree, and enthusiasm, physical strength, and passing on knowledge by the younger. On another level, this is a moving, lyrical story about the circle of life, and as such it offers a starting point for discussions about life, loss, and growing up to care for others as our elders did for us. The story also hints at recent research into tree communication, which postulates that trees are more social and sophisticated than previously thought. It also subtly encourages environmental stewardship"--